Mammal - Boyd, Polly; Hayward, Kate.; Mallard-Shaw, Elizabeth; Smithsonian Institution (New York : Dorling Kindersley, 2003)
Explains what mammals are, and provides photographs and descriptions of different mammals that live in grassland, desert, mountain, wetland, forest, island, water, and polar habitats around the world.
"Smithsonian Institution.".
Includes index.
Young Adult
Keywords: Mammals; Mammals -- Pictorial works